New early Pleistocene Alligator (Eusuchia: Crocodylia) from Florida bridges a gap in Alligator evolution - Stout, Jeremy B. (Zootaxa, 2020)
The American Alligator (Alligator mississippiensis) is one of two species of Alligator in the modern world. It is only distantly related to the other extant species (A. sinensis), with much closer relatives known from the geologic past of North America. A disparity exists, though, in the fossil record between A. mississippiensis and its close relative, the late Miocene (?)—early Pliocene A. mefferdi. While A. mississippiensis is known from the mid-Pleistocene and later, few Alligator remains were known from the earliest Pleistocene of North America until the discovery of the Haile 7C and 7G early Pleistocene (Blancan Land Mammal Age) sites from Alachua County, Florida. The Haile alligators exhibit a suite of characters from both A. mississippiensis and A. mefferdi, displaying intermediate morphology in time. The Haile alligators are distinct from either of the aforementioned taxa, and a new species, Alligator hailensis is suggested, bridging an important gap in the evolution of the American Alligator.